Genetic variability of two populations of Pseudoplatystoma reticulatum from the Upper Paraguay River Basin - De Abreu, Marcia Matos; Pereira, Luiz Henrique Garcia [UNESP]; Vila, Vilma Barretto; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (FapUNIFESP (SciELO), 2009)
Catfishes of the genus Pseudoplatystoma are very important species due to both their high commercial value and their ecological role as voracious predators. They undertake lengthy migratory movements during their life-cycle, this including reproductive migration which occurs from October to December in the rainy season. In the present study, seven microsatellite loci were analyzed to access genetic variability in two samples of P. reticulatum from the Upper Paraguay Basin. The loci were highly polymorphic (mean = 7.28). According to all analysis, the two samples of P. reticulatum revealed pronounced genetic differentiation. Fst value was 0.2290, Rst value 0.1067 and AMOVA 22.90% (Fst) and 10.67% (Rst), all being highly significant (p < 0.001). The division of the fishes into two groups was confirmed by microsatellite multi-locus Bayesian assignment testing. The results obtained present evidence of genetic structuring in a P. reticulatum population. Copyright © 2009, Sociedade Brasileira de Genética.
Keywords: Fish; Homing; Microsatellite; Population genetics; Population structure